Price dynamics and market integration of tomato markets in India - G Hemanth Kumar; T M Gajanana (Agricultural Economics Research Review, 2023)
The current study uses the Johansen co-integration, Vector Error Correction model, and Granger causality test to investigate the level of market integration and price transmission in the key tomato markets in India. From January 2010 to March 2020, the study examined weekly average tomato pricing data (Rs/quintal) collected from specific markets in Kolar, Srinivaspur, Bangalore (production markets), Chennai, Kolkata, Pimpalgaon, and Delhi (consumption markets). The findings provided substantial evidence for the co-integration and interdependence of these market places in India. However, the rate of price adjustment was found to be moderate across all markets, and as a result, prices only correct a tiny portion of the market’s disequilibrium, with external and internal forces accounting for the majority of the correction. Since there is unidirectional causality from Kolkata to Kolar markets, it makes it necessary for future research to examine the influence of internal and external factors like market infrastructure. It also calls for improving information technology to allow for the regular flow of market information to assist farmers in increasing their income.